Keeping a Critical Eye on the Science and the Regulation of Oral Drug Absorption: A Review - Macheras, Panos; Karalis, Vangelis; Valsami, Georgia (JOURNAL OF PHARMACEUTICAL SCIENCES, 2013)
This review starts with an introduction on the theoretical aspects of biopharmaceutics and developments in this field from mid-1950s to late 1970s. It critically addresses issues related to fundamental processes in oral drug absorption such as the complex interplay between drugs and the gastrointestinal system. Special emphasis is placed on drug dissolution and permeability phenomena as well as on the mathematical modeling of oral drug absorption. The review ends with regulatory aspects of oral drug absorption focusing on bioequivalence studies and the US Food and Drug Administration and European Medicines Agency guidelines dealing with Biopharmaceutics Classification System and Biopharmaceutic Drug Disposition Classification System. (C) 2013Wiley Periodicals, Inc. and the American Pharmacists Association
Keywords: ADME; BCS; BDDCS; Bioavailability; bioequivalence; gastrointestinal transit; oral absorption; Permeability; Solubility